2003
DOI: 10.1097/00002826-200305000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Apomorphine Infusion and the Long-Duration Response to Levodopa in Advanced Parkinson's Disease

Abstract: The authors investigated the long-duration response to levodopa in advanced Parkinson's disease. Eight patients with advanced Parkinson's disease disabled by severe ON/OFF fluctuations treated by chronic daytime subcutaneous apomorphine infusion with supplemental oral levodopa were studied. On day 1, oral levodopa was withdrawn at 4:00 pm and on the following morning subcutaneous apomorphine infusion was continued at the same rate without levodopa therapy. While receiving apomorphine alone, seven of the eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…This finding is in keeping with previous studies reporting that STN DBS can provide greater reduction in dopaminergic medications and ÔoffÕ time improvement than apomorphine infusion [24,25] and that jejunal levodopa can be more efficacious than apomorphine infusion to control motor fluctuations [26]. The present data are also in keeping with a previous report that apomorphine monotherapy fails to keep patients with PD in the ÔonÕ state after withdrawal of oral levodopa [27] and that only a minority of patients with continuous apomorphine infusions can withdraw all other medications [28].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in keeping with previous studies reporting that STN DBS can provide greater reduction in dopaminergic medications and ÔoffÕ time improvement than apomorphine infusion [24,25] and that jejunal levodopa can be more efficacious than apomorphine infusion to control motor fluctuations [26]. The present data are also in keeping with a previous report that apomorphine monotherapy fails to keep patients with PD in the ÔonÕ state after withdrawal of oral levodopa [27] and that only a minority of patients with continuous apomorphine infusions can withdraw all other medications [28].…”
Section: Discussionsupporting
confidence: 93%
“…26,27 This suggests that postsynaptic changes may be concomitantly or exclusively involved in the origin of LDR. It has been recently suggested that changes of the intracellular mechanism of D1 transmission due to prolonged therapy may be largely responsible of the appearance of dyskinesia.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenology of this improvement and its further decay when levodopa is stopped resembles the LDR to levodopa. These results suggest that the motor effect induced by the test dose of levodopa is sustained by levodopa LDR as has been described for the clinical effect of apomorphine in patients with advanced PD (Stocchi et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%